Physical Methods for Stimulation of Plant and Mushroom Development 2018
DOI: 10.5772/intechopen.79159
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Methods for Mushroom Fruit-Body Developments

Abstract: High-voltage electrical stimulation is effective for promotion of fruit-body development in mushroom cultivation. The high voltage applying to cultivation bed of mushroom generates intense electric field inside the bed substrate. The intense electric field accelerates the hypha move owing to the electrostatic force. As a result, some parts of hyphae are cut and scratched. The cutting and scratching of hypha work as stimulation for promotion of the fruit-body development. The promotion effect of high-voltage st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…When the frequency component of the applied pulse voltage is less than several MHz, the membrane of the cell, rather than the inside of the cell, is mainly subjected to the electric field [15]. The hyphae are accelerated and displaced according to the electric field by the electrostatic force such as a Coulomb force [16], which could induce a physical stress on the hyphae. It has been suggested that some genes encoding enzymes such as laccase and protease [17,18,19] could be upregulated by the physical stress [1,5] in the same manner as other physical stresses such as scrapping of surface hyphae, which induces fruit body formation [16,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the frequency component of the applied pulse voltage is less than several MHz, the membrane of the cell, rather than the inside of the cell, is mainly subjected to the electric field [15]. The hyphae are accelerated and displaced according to the electric field by the electrostatic force such as a Coulomb force [16], which could induce a physical stress on the hyphae. It has been suggested that some genes encoding enzymes such as laccase and protease [17,18,19] could be upregulated by the physical stress [1,5] in the same manner as other physical stresses such as scrapping of surface hyphae, which induces fruit body formation [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…The hyphae are accelerated and displaced according to the electric field by the electrostatic force such as a Coulomb force [16], which could induce a physical stress on the hyphae. It has been suggested that some genes encoding enzymes such as laccase and protease [17,18,19] could be upregulated by the physical stress [1,5] in the same manner as other physical stresses such as scrapping of surface hyphae, which induces fruit body formation [16,20]. Since the physical stress relates to the fruit body formation, the flush is accelerated and the amount of cropped fruitbody is increased in the seasons that the logs are stimulated by the voltage pulses as shown in Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of high-voltage pulsed stimulation that drive increases in fruiting body formation are not yet fully understood. However, two possible mechanisms have been explained in some previous studies [40][41][42][43][44]. One is that the mushroom mycelia were ruptured by the application of high-voltage pulses, and that physical damage to the mycelia could stimulate fruiting body formation [37,[41][42][43].…”
Section: Proximate Composition Analysismentioning
confidence: 99%
“…In other words, lightning appears to have a specific influence on the growth of mushrooms. In efforts to replicate these occurrences, previous studies have applied artificial lightning via high voltages of 30-140 kV to bed logs inoculated with shiitake mushrooms [2][3][4][5][6][7][8][9][10][11][12]. In those studies, using the surface or electrode, a large current was passed through the bed logs, resulting in shiitake mushroom growth.…”
Section: Introductionmentioning
confidence: 99%
“…without high voltage application). In addition, it has been confirmed that highvoltage electrical stimulation also positively influences shiitake mushroom growth rates [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%